Perception and Satisfaction of Undergraduate Medical Students of the Mini Clinical Evaluation Exercise Implementation in Orthopedic Outpatient Setting - Alomar AZ (Advances in Medical Education and Practice, 2022)
Abdulaziz Z Alomar Department of Orthopaedic Surgery, College of Medicine, King Saud University, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Abdulaziz Z Alomar, Department of Orthopaedic Surgery, College of Medicine, King Saud University, Riyadh, Kingdom of Saudi Arabia, Tel +966554655665, Email dr_abdulaziz@yahoo.comPurpose: The Mini Clinical Evaluation Exercise (mini-CEX) is a brief and direct observational assessment of trainee-patient interactions that helps to assess several clinical domains. There is limited evidence of mini-CEX implementation in orthopedics and undergraduate perceptions toward such an approach. This study investigated the perception of mini-CEX among undergraduate medical students through a questionnaire-based survey in an orthopedic outpatient setting.Patients and Methods: Undergraduate medical students completing their orthopedic clinical posting were invited to participate in an anonymous, self-administered questionnaire written in English to evaluate their perceptions toward mini-CEX implementation in the orthopedic outpatient setting for the 2016– 2017 academic session. The questionnaire comprised 28 closed-ended questions with a five-point Likert rating-scale, and five open-ended questions. The survey responses were analyzed for reliability, validity, and quantitative and qualitative analyses.Results: A total of 350 students completed the questionnaire; the questionnaire was proven to be valid and reliable. The closed-ended questions were designed to assess the knowledge of the mini-CEX as an assessment tool. The participants demonstrated a satisfactory understanding of the mini-CEX methodology, purpose, clarity, comprehensiveness, and as a self-assessment tool for undergraduate medical students. Instructor support for the implementation of mini-CEX appeared inadequate and was rated with non-confidence among most students. Most participants appreciated better clinical skills, which was reflected through improvements in clinical exam preparation, the Objective Structured Clinical Examination, and clinical judgment.Conclusion: Undergraduate medical students perceived the mini-CEX as an effective tool for clinical teaching in an outpatient orthopedic setting. However, most students indicated suboptimal instructor involvement in the teaching and assessment process; this raises concerns regarding inadequate direct observation and limited feedback for student performance. Additional measures are needed to ensure high quality clinical encounters, teacher training, integration with other assessment tools, and standardized coverage mini-CEX implementation in orthopedics.Keywords: mini clinical evaluation exercise, orthopedics, outpatient, undergraduate